Sistem Pendukung Keputusan Penerimaan Bantuan UMKM dengan Metode Moora: Pembuatan Sistem pendukung keputusan untuk Program Bantuan Produktif Usaha Mikro (BPUM) dengan metode MOORA pada kota Bekasi - Aulia, Risya; Hartanti, Dian (PETIR, 2024)
Due to the presence of the Covid-19 virus since March 2020, several sectors in Indonesia have been affected, including the economy. Considering the significant number and importance of Micro, Small, and Medium Enterprises (MSMEs) for the government and society, the government has provided Presidential Assistance (Banpres) by distributing Productive Micro Business Assistance (BPUM). The Bekasi City Office has not maximized the selection of MSMEs and faces difficulties in obtaining priority assistance from the government. To overcome this issue, a decision support system for MSME assistance has been developed using the Multi-Objective Optimization by Ratio Analysis (MOORA) method as a tool to facilitate the decision-making process in providing MSME assistance in Bekasi City. The evaluation of MSME assistance participants is based on several predetermined criteria, including the business owner's address according to their ID card (KTP), the business location, the field of business, registration for people's business credit loans, simultaneous registration for other forms of assistance, and previous receipt of BPUM. This research generates data on eligible MSME recipients who deserve assistance with prioritization rankings based on calculations performed in the system using the MOORA method. From the analysis of 50 data used, participant Yunita Sari obtained the top ranking with a score of 0.74.